Methodological Challenges in Conducting Cross-Cultural/Language Research with Spanish Speakers: The Role of the Researcher/Translator - Flores-Gomez, C (Peace and Conflict Studies, 2024)
With the increase in global research, it is common for researchers to investigate topics in intercultural settings, both in their own home countries and abroad. Although findings from this research are prolific, rarely are detailed examples given or practical suggestions offered, particularly in relation to the role of the translator/researcher. The significant and often undervalued role of the translator/researcher in cross cultural/language qualitative research warrants methodological considerations at the onset and throughout the research. Nonetheless, few qualitative studies transparently report the process of how the translation findings were developed. This paper addresses this gap by examining a Latinx postgraduate student’s role in the qualitative research on teacher induction in Chile. I used reflexivity to assess my positionality of insiderness and outsiderness and its influence in the process of recruitment, conducting interviews, transcription, and translation. Interviews were conducted, transcribed and analysed in Spanish. Examples of data translation that can help to identify the main issues associated with reporting the findings in English are provided. These applied examples are used to illustrate the gaps and misinterpretations possible in intercultural research. The importance of researcher’s culture competence, contextual skills and knowledge of the field of the study are highlighted. 2024: Catherine Flores and Nova Southeastern University.